2009
DOI: 10.1111/j.1753-4887.1994.tb01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition in the Nursing Home: Prevalence, Consequences, Causes and Prevention

Abstract: Approximately 5% of Americans over age 65, or 1.5 million individuals, currently reside in the nations's 20,000 nursing homes. The authors present material that lead to three conclusions about this population. First, nutritional deficiencies are common underlying causes of adverse clinical outcomes. Second, nutritional deficiencies are frequently not recognized. Third, opportunities for preventing or correcting undernutrition exist, provided that the significant and reversible nature of the nutrient deficienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(52 citation statements)
references
References 61 publications
(5 reference statements)
1
50
1
Order By: Relevance
“…Despite the quality improvement, substantial problems remain with the quality of care in nursing homes [4,22]. The literature documented quality problems ranging from malnutrition [23][24], and dehydration [25], to medication errors [26], pressure ulcers [27], and pain [28]. Hospitalizations of nursing home residents are common.…”
Section: Evidence Of Low Quality In Nursing Homes and Changes In Qualmentioning
confidence: 99%
“…Despite the quality improvement, substantial problems remain with the quality of care in nursing homes [4,22]. The literature documented quality problems ranging from malnutrition [23][24], and dehydration [25], to medication errors [26], pressure ulcers [27], and pain [28]. Hospitalizations of nursing home residents are common.…”
Section: Evidence Of Low Quality In Nursing Homes and Changes In Qualmentioning
confidence: 99%
“…The results of the BAPEN nutrition screening week found that 28-32 % of residents in care homes were malnourished (2) . However, in everyday practice malnutrition is not always identified and therefore not treated (3) . The National Institute for Health and Clinical Excellence recommends that all hospital patients and carehome residents should be weighed and measured on admission (4) and advises that this screening should include BMI and unplanned weight loss.…”
mentioning
confidence: 99%
“…MUST is based on BMI and weight loss (2) . It is a validated, objective, screening tool that identifies adults who are underweight and at risk of malnutrition and provides guidelines for management.Malnutrition is not always identified, therefore not treated (3) . The cost of malnutrition in the UK has been estimated to be £7.3 billion (4) : more than twice the cost of obesity.…”
mentioning
confidence: 99%